Application of the boundary element method to modeling of crack propagation trajectories - Jackiewicz, Jacek (Computer Assisted Methods in Engineering and Science, 2023)
The present paper further develops the boundary element technique to provide an efficient and accurate method of analysing the crack propagation processes in 2-D linear elastic structures. Based on both the direct boundary integral equations, for source points located on the external boundary of the plane elastic region, and the indirect boundary integral equations, for the resultant forces acting on one side of the crack surfaces, this technique allows to avoid problems associated with other numerical methods for fracture mechanics computation. In the first part of this paper, the proposed boundary element technique and also the strain energy density criterion, which determines the crack increment in a mixed-mode loading situations, are described. In the second part, two numerical examples are enclosed to demonstrate the capabilities of the boundary element technique as a tool for modelling an arbitrary crack, predicting its growth and updating the model geometry to simulate the next crack increment.